An Examination on Online Learning Adoption of Postgraduate Students in Chengdu, China During COVID-19 - Lyu, Yaze (Scholar: Human Sciences, 2023)
Purpose: Online learning has dramatically increased adoption in the educational sector during the COVID-19 pandemic. This study examines the online learning adoption of college students in Chengdu, China. Technology acceptance model (TAM) and the unified theory of acceptance and use of technology (UTAUT) incorporates perceived ease of use, perceived usefulness, attitude, social influence, facilitating conditions, behavioral intention, and use behavior. Research design, data, and methodology: The target population is 500 postgraduate students in the top three universities in Chengdu. The sample techniques are purposive, stratified random, convenience, and snowball samplings. The Item Objective Congruence (IOC) Index and the pilot test (n=50) by Cronbach’s Alpha were used to ensure content and construct validity. The data analysis was conducted by Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Results: The findings show that perceived ease of use significantly impacts perceived usefulness. Behavioral intention strongly and significantly impacts use behavior. Behavioral intention is significantly impacted by perceived ease of use, usefulness, attitude, social influence, and facilitating conditions. Conclusions: The virtual classroom has continued in China due to China’s “Zero-COVID” Policy after the decline of health and safety restrictions. Therefore, this study addresses the factors to improve the online learning adoption rate.